Indocalamus chongzhouensis (Poaceae: Bambusoideae), a new synonym of I. emeiensis: evidence from morphology and complete chloroplast genome data - Gao, Li-Qin; Li, Yong-Long; Guo, Chun-Ce; Yang, Guang-Yao; Zhang, Wen-Gen (Phytotaxa, 2022)
Based on evidence from morphology, micromorphology of the abaxial leaf epidermis and phylogenetic analysis by using complete chloroplast genome data, it was found that Indocalamus chongzhouensis is conspecific with I. emeiensis, and should be synonymized with the latter. An updated description, illustrations, and a distribution map are also provided.